“What the One Thing Shows Me in the Case of Two Things”: Comparison as Essential to a Proper Academic Study of Religion - Gill, Sam D. (Method & theory in the study of religion, 2022)
Comparison is a fundamental operation in the milieu of the remarkable abilities of human beings to transcend themselves in acts of perception and the accumulation of knowledge. Comparison is holding together things that are at once the same and different. The very possibility of the copresence of same and different, of is and is not, is a gift of human biology and evolution. Humans compare because it is our distinctive nature to do so. Academics have the added responsibility of being self-aware, self-reflective, and articulate when comparing. This article develops a rich theory of comparison in conjunction with detailed reflections on late nineteenth century encounters of European-Australians and Aborigines in Central Australia. The intent is to advance our understanding of comparison and also to articulate in the practical terms of method what is involved in comparison, arguing most generally that comparison is of the fabric of any proper study of religion.